"THE IMPORTANCE OF FAMILY IN PERSONAL FORMATION AND SOCIAL SUCCESS""THE IMPORTANCE OF FAMILY IN PERSONAL FORMATION AND SOCIAL SUCCESS" (Universal International Scientific Journal, 2026)
In this article, the family is an important social environment in the process of personality formation. The family is the primary place of upbringing of a person, where the child learns moral values, social norms and life skills. This topic highlights the role of the family in the spiritual, moral and intellectual development of a person, as well as its impact on his future social success. Parental education, a healthy environment in the family, mutual respect and support are important factors in the formation of a person as an active, responsible and successful person in society. Therefore, proper upbringing and a positive environment in the family are of great importance for the harmonious growth of a person.
Keywords: Family, personality formation, upbringing, social environment, spiritual values, parenting, social success, personal development, family relationships, harmonious generation.